Kinesin Family Member C1 Increases Temozolomide Resistance of Glioblastoma Through Promoting DNA Damage Repair. (12th February 2021) - Wu, Jianheng; Wang, Xinjun; Yuan, Xiaowei; Shan, Qiao; Wang, Zhen; Wu, Yuehui; Xie, Jingwei
Glioblastoma (GBM) is one of the most frequent primary malignant brain tumors with a poor prognosis. Unfortunately, due to the intrinsic or acquired chemoresistance of GBM cells, it easily becomes refractory disease and tumors are easy to recur. Therefore, it is critical to elucidate the molecular mechanisms underlying the chemoresistance of GBM cells to discover more efficient therapeutic treatments. Kinesin family member C1 (KIFC1) is a normal nonessential kinesin motor that affects the progression of multiple types of cancers. However, whether KIFC1 have a function in GBM is still unexplored. Here we found that KIFC1 was upregulated in human temozolomide (TMZ)-resistant GBM tissues. KIFC1 silencing is sufficient to inhibit GBM cell proliferation and amplify TMZ-induced repression of cell proliferation. Mechanistically, KIFC1 silencing contributed to DNA damage, cell cycle arrest, and apoptosis through regulating Rad51, Akt, and DNA-PKcs phosphorylation. We also noticed that KIFC1 silencing also inhibited tumor formation and increased TMZ sensitivity through regulating Ki67, Rad51, γ-H2AX, and phosphorylation of AKT in vivo . Our findings therefore confirm the involvement of KIFC1 in GBM progression and provide a novel understanding of KIFC1-Akt axis in the sensitivity of GBM to chemotherapy.